2012
DOI: 10.1017/s1368980012003175
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Breakfast Quality Index (BQI) for children and adolescents

Abstract: Objective: To propose and apply an instrument to assess the breakfast quality of children and adolescents in the Mediterranean area. Design: Randomized, cross-sectional survey of breakfast consumption using a validated semi-quantitative FFQ administered at school by trained dietitians between Tuesday and Friday. A Breakfast Quality Index (BQI) score was developed, assigning a positive value to the consumption of cereals, fruit, vegetables, dairy products, MUFA, Ca and compliance with energy recommendations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 43 publications
3
56
2
1
Order By: Relevance
“…Based on food frequency questionnaire data and on a population-based study of adolescents from two different regions in Spain, Monteagudo et al [22] found that the contribution of breakfast to daily energy intake ranged from 21.14% (girls aged 14 to 17 years) to 25.81% (boys aged 10 to 13 years), which shows slightly higher proportions than those found in the present study. However, it is worth highlighting the different methods used in these two studies to obtain food consumption data.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Based on food frequency questionnaire data and on a population-based study of adolescents from two different regions in Spain, Monteagudo et al [22] found that the contribution of breakfast to daily energy intake ranged from 21.14% (girls aged 14 to 17 years) to 25.81% (boys aged 10 to 13 years), which shows slightly higher proportions than those found in the present study. However, it is worth highlighting the different methods used in these two studies to obtain food consumption data.…”
Section: Discussioncontrasting
confidence: 72%
“…However, there were differences according to income and the macro-regions of the country. The contribution of breakfast to daily energy intake was slightly lower than those reported in similar studies [21,22]. Milk was the fourth most commonly consumed food all over the country, and its consumption was three times higher in the Southeastern and CentralWestern regions than in the Northern region.…”
Section: Discussioncontrasting
confidence: 51%
“…The dietary assessment method used in each study is presented in Table 2. The studies that were analysed in the systematic review were based on the collection of dietary information through the application of 24-h recalls (25) , food diaries (29) , FFQ (26) , menus (23) , weighted foods (27,28) and meal screeners (30) . The methods observed for data collection regarding dietary intake are the ones traditionally used for research in nutrition, with exception of the meal screener, which was proposed and validated especially for the development of the meal quality index in the study conducted by Fulkerson et al (30) .…”
Section: Dietary Assessment Methodsmentioning
confidence: 99%
“…The type of meal evaluated in each study is presented in Table 2. The Breakfast Quality Index (26) and the Breakfast Score (25) were specifically developed to evaluate the nutritional quality of breakfasts consumed by children and adolescents, and should not be used to evaluate other types of meals. The components of these indices were based on foods typically consumed at breakfast, excluding other food groups.…”
Section: Type Of Meal Evaluatedmentioning
confidence: 99%
See 1 more Smart Citation